Does outdoor air pollution induce new cases of asthma? Biological plausibility and evidence; a review - GOWERS, ALISON M.; CULLINAN, PAUL; AYRES, JON G.; ANDERSON, H. ROSS; STRACHAN, DAVID P.; HOLGATE, STEPHEN T.; MILLS, INGA C.; MAYNARD, ROBERT L. (Respirology (Carlton, Vic.), 2012)
ABSTRACT It is widely accepted that air pollution can exacerbate asthma in those who already have the condition. What is less clear is whether air pollution can contribute to the initiation of new cases of asthma. Mechanistic evidence from toxicological studies, together with recent information on genes that predispose towards the development of asthma, suggests that this is biologically plausible, particularly in the light of the current understanding of asthma as a complex disease with a variety of phenotypes. The epidemiological evidence for associations between ambient levels of air pollutants and asthma prevalence at a whole community level is unconvincing; meta‐analysis confirms a lack of association. In contrast, a meta‐analysis of cohort studies found an association between asthma incidence and within‐community variations in air pollution (largely traffic dominated). Similarly, a systematic review suggests an association of asthma prevalence with exposure to traffic, although only in those living very close to heavily trafficked roads carrying a lot of trucks. Based on this evidence, the UK's Committee on the Medical Effects of Air Pollutants recently concluded that, overall, the evidence is consistent with the possibility that outdoor air pollution might play a role in causing asthma in susceptible individuals living very close to busy roads carrying a lot of truck traffic. Nonetheless, the effect on public health is unlikely to be large: air pollutants are likely to make only a small contribution, compared with other factors, in the development of asthma, and in only a small proportion of the population.